The performance of evacuated tube solar collector (ETSC) using ceo / water nanofluid / Seow Khai Tze - Seow , Khai Tze (2018)
The interest of researchers on the research of solar technology have increased tremendously from year to year due to a serious pollution to the environment caused by the emission of coal and fuels. Evacuated tube solar collector (ETSC) gain interest by the researchers because it have a lower heat loss and can achieve higher temperature compared to flat plate solar collector (FPSC). Implementing nanofluid to the ETSC have increased from years to years because nanofluid can enhance the performance and increase the efficiency of the solar collector as they have a higher thermal conductivity compared with distilled water. A mean diameter of 25nm (10-9m) of cerium (IV) oxide (CeO2) nanoparticles were used in this research of study. The stability of the nanofluid was tested by using the sedimentation method. It is the most common and cost saving method. The CeO2 nanofluid can stable up to 28 days. Three different concentration of nanofluid were synthesized comprising of 0.02%, 0.04% and 0.06% volume concentration respectively. This research of study were carried out at University of Malaya (UM). The experiment was conducted at sunny day from 0900 morning to 1800 evening. The thermal efficiency of the solar collector were carried out by using different flow rates that are 0.5L/min, 1.0L/min and 1.5L/min. The inlet temperature, outlet temperature, ambient temperature, solar radiation and etc. were recorded throughout the experiment for analysis of the performance of ETSC. The collector showed the highest efficiency of 73.46% with the use of 0.06% CeO2 nanofluid, which is 27.63% higher compared to the distilled water at volumetric flow rates of 1.5L/min. From the experiment, we can concluded that the higher concentration of the nanofluid, the higher heat gain, the higher solar efficiency of the solar collector can achieved.